“The Italian Study on Recovery 2” Phase 1: Psychometric Properties of the Recovery Assessment Scale (RAS), Italian Validation of the Recovery Assessment Scale - Boggian, Ileana; Lamonaca, Dario; Ghisi, Marta; Bottesi, Gioia; Svettini, Alessandro; Basso, Luigi; Bernardelli, Katia; Merlin, Silvia; Liberman, Robert Paul; , S.I.R. 2 group; Boggian, Ileana; Lamonaca, Dario; et al. (Frontiers in Psychiatry, 2020)
Background Recovery is related to the idea of developing personal potentials and regaining a valid social role even with limitations caused by mental illness. A whole understanding of this subjective and dynamic process is still difficult, and instruments are needed in order to test out the recovery process, which are still only marginally used in our country. Aims The Italian Study on Recovery is the first study aimed at confirming the validity of the Italian version of the Recovery Assessment Scale (RAS), an instrument developed with the goal of detecting recovery among patients. Method This multicentric research involved several Mental Health Services from various parts of Italy. The first phase of the study consisted in the administration of the Italian translation of RAS, previously used in a pilot study conducted in 2009. RAS was administered to 219 patients diagnosed with psychosis, whose mental disorder lasted for at least five years. Results Findings supported the good psychometric properties of the Italian version of RAS, demonstrating its capability of identifying patients matching the “in recovery” operational criteria. Conclusions In consideration of the results highlighting the good psychometric properties of RAS, the present study may contribute to the diffusion of instruments to be included in Mental Health Service planning in the Italian context, in order to start a recovery-oriented transformation.